2008
DOI: 10.1091/mbc.e08-02-0139
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 Promotes Growth of Colon Cancer Cells via Repression of p21

Abstract: The class II Histone deacetylase (HDAC), HDAC4, is expressed in a tissue-specific manner, and it represses differentiation of specific cell types. We demonstrate here that HDAC4 is expressed in the proliferative zone in small intestine and colon and that its expression is down-regulated during intestinal differentiation in vivo and in vitro. Subcellular localization studies demonstrated HDAC4 expression was predominantly nuclear in proliferating HCT116 cells and relocalized to the cytoplasm after cell cycle ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
174
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 58 publications
(141 reference statements)
3
174
1
1
Order By: Relevance
“…However, in SiHa cells p300 loses function for mutation (27). A review of the literature showed that HDAC3-HDAC4-N-CoR/SMRT is a complex that plays a critical role in the regulation of histone acetylation associated with the p21 promoter, as HDAC4 or SMRT down-regulation results in increased histone H3 acetylation at the proximal p21 promoter (28). Our preliminary result proved that NDGA significantly down-regulated SMRT transcription.…”
Section: Discussionsupporting
confidence: 51%
“…However, in SiHa cells p300 loses function for mutation (27). A review of the literature showed that HDAC3-HDAC4-N-CoR/SMRT is a complex that plays a critical role in the regulation of histone acetylation associated with the p21 promoter, as HDAC4 or SMRT down-regulation results in increased histone H3 acetylation at the proximal p21 promoter (28). Our preliminary result proved that NDGA significantly down-regulated SMRT transcription.…”
Section: Discussionsupporting
confidence: 51%
“…As HDAC4 alone is enzymatically inactive, it may suppress p21 WAF1/Cip1 transcription by recruiting catalytically active HDACs into transcriptional corepressor complexes such as HDAC3-NCoR/SMRT (Fischle et al, 2002). While we were preparing this paper, such a model of p21 WAF1/Cip1 repression mediated by HDAC4 through association with the catalytically active HDAC3-N-CoR/SMRT corepressor complex has been shown in colon cancer cells (Wilson et al, 2008). As HDAC3 silencing did not increase p21 WAF1/Cip1 expression in IGROV-1 cells (Figure 1b), it is also possible that the mechanism by which HDAC4 represses the p21 WAF1/Cip1 promoter varies between cell types.…”
Section: Discussionmentioning
confidence: 94%
“…Previous results have shown that class-IIa HDACs can control CDKN1A expression (Liu et al, 2009;Mottet et al, 2009;Saramaki et al, 2009;Wilson et al, 2008); however, the mechanisms involved are debated. MEF2-binding sites are present in the genomic regions surrounding CDKN1A.…”
Section: Discussionmentioning
confidence: 99%